2023
DOI: 10.3389/fnins.2023.1156453
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of probiotics for the double-edge effect of cefazolin on postoperative neurocognitive disorders by rebalancing the gut microbiota

Abstract: IntroductionEmerging data suggest that perioperative gut dysbiosis is prevalent and may be associated with postoperative neurocognitive disorders (PND). Antibiotics and probiotics are key factors influencing the microbiota. Many antibiotics have anti-microorganisms and direct anti-inflammatory properties, which may have cognitive repercussions. NLRP3 inflammasome activation has been reported to be involved with cognitive deficits. This study aimed to determine the effect and mechanism of probiotics on neurocog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Furthermore, supplementation with probiotics improved neuroinflammation and cognitive impairment in surgery. 192 , 193 Yang et al. 194 found that probiotic preparations improved memory impairment in aging mice.…”
Section: Microbiota‐based Implications For Therapeutic Interventionsmentioning
confidence: 99%
“…Furthermore, supplementation with probiotics improved neuroinflammation and cognitive impairment in surgery. 192 , 193 Yang et al. 194 found that probiotic preparations improved memory impairment in aging mice.…”
Section: Microbiota‐based Implications For Therapeutic Interventionsmentioning
confidence: 99%
“…PND is a serious clinical syndrome occurring during the perioperative period and poses a heavy medical and socioeconomic burden to the families of patients and the society. Both clinicians and scientists around the world made efforts to expand the definition of PND from perioperative delirium (POD) and post-operative cognitive disorders (POCD) [ 2 ] to perioperative neurocognitive disorders (PND). In 2018, the Nomenclature Consensus Working Group proposed that preoperative or postoperative neurocognitive disorders should be collectively assigned to ‘perioperative neurocognitive disorders’ according to DSM-5 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%